Building A Disaster Prepared Village Community To Reduce The Risk Of A Landslide Disaster In Sumurup Village, Bendungan District, Trenggalek Regency - Rizkyah Isnaini (Jurnal Biosains Pascasarjana, 2022)
This mentoring research describes the reality of people's lives who have low awareness of natural disaster response. The problems that arise in the community are the lack of public awareness in tackling and dealing with disasters, the absence of a disaster emergency response and response system, and the absence of village government policies that focus on managing landslides. The purpose of this empowerment is to find a strategy in building a resilient community for landslide natural disasters to be more independent in handling and preventing disaster events in Sumurup Village. This study refers to a research approach using the PAR method. Namely making changes in the form of education and training in landslide risk reduction in order to provide a basic understanding of disaster risk reduction by making disaster-prone maps. As well as disaster simulation training accompanied by determining evacuation routes, and installing danger signs. In addition, by advocating village government policies to create funding rules for disaster management. With a series of activities that have been carried out with the community so as to create a strong and independent community attitude in dealing with natural disasters. These activities have resulted in improvements and changes in community capacity, especially for communities directly affected by disasters in reducing the risk of landslides.